2020
DOI: 10.1177/0363546520956292
|View full text |Cite
|
Sign up to set email alerts
|

Can We Identify Why Athletes Fail to Return to Sport After Hip Arthroscopy for Femoroacetabular Impingement Syndrome? A Systematic Review and Meta-analysis

Abstract: Background: No previous systematic review has focused on the athletes who fail to return to sport after hip arthroscopy for femoroacetabular impingement syndrome (FAIS). Purpose: To review the literature on the athletes who fail to return to sport after hip arthroscopy for FAIS to determine the rate of nonreturning athletes and explore the reasons for their inability to return to sport after arthroscopic FAI surgery. Study Design: Systematic review and meta-analysis. Methods: Three electronic databases were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…5 However, optimal performance in return to preinjury performance may not be as high, with reports ranging from 30% to 80% return to full performance. 6,17,49 Additionally, there is currently a paucity of literature examining variations in patients' postoperative trajectories of recovery.…”
mentioning
confidence: 99%
“…5 However, optimal performance in return to preinjury performance may not be as high, with reports ranging from 30% to 80% return to full performance. 6,17,49 Additionally, there is currently a paucity of literature examining variations in patients' postoperative trajectories of recovery.…”
mentioning
confidence: 99%
“…It is well known that longer symptom duration is associated with inferior outcomes after FAIS surgery and younger age has previously been associated with higher RTS. 14 , 16 , 26 The reason for the absence of relationship in this study may relate to the sample size of the study population.…”
Section: Discussionmentioning
confidence: 88%
“…There are multiple aspects affecting a player’s choice to RTS and players may retire for other reasons not related to hip pain. 26 Often, it is difficult to decide if persistent hip pain is the preventive factor for not returning to sport after surgery, and the reason why some athletes do not RTS remains unknown. Future prospective studies are warranted, including presurgical expectations of returning to sport and postsurgical evaluations of limitations to return, including the reason for not returning.…”
Section: Discussionmentioning
confidence: 99%
“…Although outcomes of athletes who RTS are heavily studied, much less is known about athletes who fail to RTS or choose to retire from competitive sports. 67 Weber et al, 67 in a systematic review and meta-analysis, sought to determine the rate of nonreturning athletes who undergo hip arthroscopy and to explore the reasons for their inability to RTS. The investigators found that in the primary setting, the proportion of athletes who did not RTS because of hip-related issues was significantly greater than the percentage of athletes who did not return for reasons unrelated to their hip (74.3% vs 22.3%; P < .0001).…”
Section: Discussionmentioning
confidence: 99%